Prediction of hepatocellular carcinoma risk in patients with chronic liver disease from dynamic modular networks - Chen, Yinying; Yang, Wei; Chen, Qilong; Liu, Qiong; Liu, Jun; Zhang, Yingying; Li, Bing; Li, Dongfeng; Nan, Jingyi; Li, Xiaodong; Wu, Huikun; Xiang, Xinghua; et al. (Journal of translational medicine, 2021)
Background Discovering potential predictive risks in the super precarcinomatous phase of hepatocellular carcinoma (HCC) without any clinical manifestations is impossible under normal paradigm but critical to control this complex disease. Methods In this study, we utilized a proposed sequential allosteric modules ( AMs )-based approach and quantitatively calculated the topological structural variations of these AM s. Results We found the total of 13 oncogenic allosteric modules ( OAMs ) among chronic hepatitis B (CHB), cirrhosis and HCC network used SimiNEF. We obtained the 11 highly correlated gene pairs involving 15 genes (r > 0.8, P < 0.001) from the 12 OAMs (the out-of-bag (OOB) classification error rate < 0.5) partial consistent with those in independent clinical microarray data, then a three-gene set (cyp1a2-cyp2c19-il6) was optimized to distinguish HCC from non-tumor liver tissues using random forests with an average area under the curve (AUC) of 0.973. Furthermore, we found significant inhibitory effect on the tumor growth of Bel-7402, Hep 3B and Huh7 cell lines in zebrafish treated with the compounds affected those three genes. Conclusions These findings indicated that the sequential AMs -based approach could detect HCC risk in the patients with chronic liver disease and might be applied to any time-dependent risk of cancer.